The Impact of Implementing Mind Mapping to Enhance Vocabulary Acquisition in Arabic Language Learning at Universiti Teknologi MARA (UiTM) - Muhammad Dzulfikri Al Imany; Yusraini; Mustar; Maslinawati Mohamad (PPPBA, 2024)
This study explores the use of mind maps as an engaging and creative note-taking tool that incorporates words, colors, lines, and images. The primary goal of mind maps is to create visual and graphic representations of topics, ultimately facilitating note-taking, reinforcement, and retrieval of learned information. The use of mind maps supports visual learning styles and has been shown to improve students' speaking skills. The results of the study indicate a 42% improvement in speaking skills, as well as increased learning motivation, evidenced by a decrease in boredom levels among students learning Arabic. This study suggests further development using digital technology to expand the use of mind maps in various learning contexts. This abstract provides a comprehensive overview in a concise and clear format, including the research objectives, main methods, obtained results, and recommendations for future research. تستكشف هذه الدراسة استخدام الخرائط الذهنية كأداة لتدوين الملاحظات بشكل جذاب وإبداعي باستخدام الكلمات والألوان والخطوط والصور. الهدف الرئيسي من الخرائط الذهنية هو إنشاء تمثيلات بصرية ورسومية للمواضيع، مما يسهل في النهاية تدوين الملاحظات وتعزيز واسترجاع المعلومات المتعلمة. يدعم استخدام الخرائط الذهنية أساليب التعلم البصرية وقد ثبت أنها تحسن مهارات التحدث لدى الطلاب. تشير نتائج الدراسة إلى تحسن بنسبة 42% في مهارات التحدث، بالإضافة إلى زيادة الدافع للتعلم، كما يتضح من انخفاض مستويات الملل بين الطلاب أثناء تعلم اللغة العربية. تقترح هذه الدراسة تطويرًا إضافيًا باستخدام التكنولوجيا الرقمية لتوسيع استخدام الخرائط الذهنية في سياقات التعلم المختلفة. يوفر هذا الملخص نظرة شاملة في شكل موجز وواضح، بما في ذلك أهداف البحث والأساليب الرئيسية والنتائج التي تم الحصول عليها والتوصيات للبحوث المستقبلية.